O processamento cognitivo do palavrão - Oliveira, Kiminay de (2021)
This study aims to analyze the cognitive processing of curse words in its literal and figurative meaning on the basis of the Relevance Theory and Eye Movement The studied sample consisted of 30 students and employees of UTFPR in Ponta Grossa. Data collection consisted of two instruments: 1) Visual Cognitive Processing Test on the tracker; 2) Post-collection questionnaire. This research had as specific objectives: to show the origin of curse words and their meaning; present theories of Pragmatics that explain the use of the them; describe the research that presents the interface between Eye Movements and Linguistics; collect eye movement data while reading sentences in which the target words are found in two figurative (curse words) and literal (dictionary sense) contexts; apply a post-collection questionnaire; analyze eye movements while reading the curse words; analyze the target words under the bias of Relevance Theory; compare the result of the cognitive processing of the Relevance Theory with that of the Eye movements and analyze the responses of the usability questionnaire through the RT. The analyzes were composed of heat maps, graphs on the average percentage duration of fixations and analysis of the sentences through the deductive mechanisms Modus Ponens. Through the development of this research, it was observed that the procedures of human interpretation in relation to the expletive attest that the eye movements provide real data of the cognitive processing while the deductive mechanisms help in the explanation of the inferential processes. Therefore, the interpretation depends on the cognitive context restricted by the search for relevance, in which the cognitive effect tends to overcome the cognitive effort. It was obtained in the analysis results that curse words can be used as part of a communicative strategy to facilitate human interaction, given that curse words in the figurative sense are easy to be interpreted. Based on all the research and the results achieved, a pedagogical proposal for High School and Higher Education was created, entitled “The educated curse word”, composed of strategies and tools on how to work on the curse words in the school life routine.